2015
DOI: 10.1021/acs.jafc.5b00857
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Encapsulated Echium Oil (Echium plantagineum) Increases the Content of Stearidonic Acid in Plasma Lipid Fractions and Milk Fat of Dairy Cows

Abstract: The objective of this study was to evaluate the impact of feeding lipid-encapsulated echium oil (EEO) on animal performance and milk fatty acid profile. Twelve Holstein dairy cows were used in a 3 × 3 Latin Square design with 14 day periods. Treatments were a control diet (no supplemental fat), 1.5% dry matter (DM) as EEO and 3.0% DM as EEO. Treatments had no negative effect on animal performance (dry matter intake, milk yield, and fat yield). The milk fat content of total n-3 fatty acids and stearidonic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
(95 reference statements)
5
21
1
Order By: Relevance
“…Data reporting the effects of dietary treatments on the FA compositions of TAG and NEFA fractions are scarce, whereas these FA are those available for mammary uptake. Otherwise, a recent study conducted on lactating cows supplemented with Echium oil rich in PUFA reported the absence of an increase in n‐3 PUFA in plasma TAG when the quantity of ingested oil was doubled. These data raised the question of the location of the absorbed dietary FA as well as their metabolism in the plasma.…”
Section: Effects Of Dietary Lipids On Lipid Metabolism In Dairy Ruminmentioning
confidence: 93%
“…Data reporting the effects of dietary treatments on the FA compositions of TAG and NEFA fractions are scarce, whereas these FA are those available for mammary uptake. Otherwise, a recent study conducted on lactating cows supplemented with Echium oil rich in PUFA reported the absence of an increase in n‐3 PUFA in plasma TAG when the quantity of ingested oil was doubled. These data raised the question of the location of the absorbed dietary FA as well as their metabolism in the plasma.…”
Section: Effects Of Dietary Lipids On Lipid Metabolism In Dairy Ruminmentioning
confidence: 93%
“…FA composition of feed and milk samples was determined as described by Bainbridge et al . [ 26 ]. The content (g/kg) of individual FA in milk was calculated as follows, assuming milk fat to be 93.3% of FA [ 27 ]: Total milk FA yield ( g / d ) = [ Milk fat yield ( kg / d ) x 1000] x 0.933 …”
Section: Methodsmentioning
confidence: 99%
“…Forage and milk FA compositions were determined by the method of Bainbridge et al (Bainbridge, Lock, & Kraft, 2015). A typical chromatograph produced by this method is presented in Supplemental Figure 1…”
Section: Milk and Forage Fa Analysismentioning
confidence: 99%